2022
DOI: 10.1186/s12905-022-01594-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to different types of mass media and timing of antenatal care initiation: insights from the 2016 Uganda Demographic and Health Survey

Abstract: Background Early initiation of antenatal care (ANC) within the first trimester is highly recommended in the current 2016 World Health Organization (WHO) guidelines. Mass media has the potential to promote early initiation of ANC because it has been used successfully in several programs. However, there is paucity of literature on the effect of exposure to different types of media on the timing of ANC initiation in Uganda. Our study aimed at exploring associations between exposure to different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 46 publications
4
31
0
Order By: Relevance
“…So, it would be an interesting variable to add in future surveys because of the enormous advantages it carries over the traditional media [ 65 ]. In line with earlier studies [ 69 ], our current analysis shows that there are variations in the influence of different types of mass media, with radio and television being more effective and the policy makers may need to pay attention it [ 67 ]. Much as this analysis of secondary data did not reveal any association between socioeconomic status and the complete continuum of maternal care, exposure to mass media may be interpreted as a proxy indicator for women more likely to be of a higher social economic status and more likely to use maternal services [ 70 ].…”
Section: Discussionsupporting
confidence: 84%
“…So, it would be an interesting variable to add in future surveys because of the enormous advantages it carries over the traditional media [ 65 ]. In line with earlier studies [ 69 ], our current analysis shows that there are variations in the influence of different types of mass media, with radio and television being more effective and the policy makers may need to pay attention it [ 67 ]. Much as this analysis of secondary data did not reveal any association between socioeconomic status and the complete continuum of maternal care, exposure to mass media may be interpreted as a proxy indicator for women more likely to be of a higher social economic status and more likely to use maternal services [ 70 ].…”
Section: Discussionsupporting
confidence: 84%
“…Exposure to newspapers/magazines was associated with higher odds of receiving all ANC components. Previous studies have showed a positive association between exposure to mass media and maternal health utilisation including ANC [ 58 61 ]. Exposure to mass media leads to positive health seeking behavioral changes through sharing information about the benefits of timely and frequent ANC contacts [ 3 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Majority of these maternal deaths are preventable through skilled birth attendance and increased antenatal care (ANC) contacts. 1,3,4 Focussed ANC has been shown to increase the likelihood of skilled birth attendance 5,6 and also gives health workers an opportunity to advise pregnant women on essential pregnancy care to reduce malnutrition, stillbirths, maternal mortality and morbidity, and neonatal deaths. 1,7 Proper access to ANC has been shown to reduce maternal mortality by up to 8 per 1000 live births.…”
Section: Introductionmentioning
confidence: 99%
“…8 Although the number of contacts does not guarantee good quality of ANC, in theory, the more points of contact that a woman has with a well-functioning and effective health system, the higher the likelihood of earlier prevention, detection and treatment of potential pregnancy complications. 3,8 ANC quality is tracked by three dimensions: the number of visits, timing of initiation and content of the care received. 9 The timing of initiation of ANC, ANC provider and the total number of ANC contacts have been shown to affect the content and quality of ANC received.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation